2016
DOI: 10.1093/molbev/msw232
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Evolution of Cold Tolerance Within Drosophila melanogaster

Abstract: Drosophila melanogaster originated in tropical Africa before expanding into strikingly different temperate climates in Eurasia and beyond. Here, we find elevated cold tolerance in three distinct geographic regions: beyond the well-studied non-African case, we show that populations from the highlands of Ethiopia and South Africa have significantly increased cold tolerance as well. We observe greater cold tolerance in outbred versus inbred flies, but only in populations with higher inversion frequencies. Each co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
94
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 45 publications
8
94
1
Order By: Relevance
“…van Delden and Kamping (1991) also found effects of In(2L)t on fitness traits, showing that inverted homokaryotypes had longer development time and lower body weight than the heterokaryotypes and noninverted standard homokaryotypes. Weeks et al (2002) found that the frequency of In(3L)P is negatively associated with cold resistance-an observation consistent with the findings of Anderson et al (2003) and Durmaz et al (2018) for In(3R)Payne and those of Pool et al (2017) showing that African highland populations are more cold-tolerant but have lower frequencies of common inversion polymorphisms. Given the tropical African origin of common cosmopolitan inversions, and their typically higher frequency in warmer climates, the negative relationship between their frequency and cold tolerance is intriguing and strongly points to a direct causal involvement of these chromosomal rearrangements in climate adaptation.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…van Delden and Kamping (1991) also found effects of In(2L)t on fitness traits, showing that inverted homokaryotypes had longer development time and lower body weight than the heterokaryotypes and noninverted standard homokaryotypes. Weeks et al (2002) found that the frequency of In(3L)P is negatively associated with cold resistance-an observation consistent with the findings of Anderson et al (2003) and Durmaz et al (2018) for In(3R)Payne and those of Pool et al (2017) showing that African highland populations are more cold-tolerant but have lower frequencies of common inversion polymorphisms. Given the tropical African origin of common cosmopolitan inversions, and their typically higher frequency in warmer climates, the negative relationship between their frequency and cold tolerance is intriguing and strongly points to a direct causal involvement of these chromosomal rearrangements in climate adaptation.…”
supporting
confidence: 79%
“…For example, in African populations of D. melanogaster the four common polymorphisms tend to be more frequent in tropical lowland sites as compared to high-altitude locations, perhaps suggesting that the continent-wide latitudinal clines are locally mirrored by altitudinal clines (Pool et al, 2017; also see discussion in Klepsatel, Gáliková, Huber, & Flatt, 2014;and Fabian et al, 2015). In addition, there is evidence that several inversions, especially In(2L)t and In(3L) P, exhibit longitudinal clinality, although such clines tend to be less pronounced and often covary with latitudinal patterns (see Figure 2, Supporting Information Table S2; Aulard et al, 2002;Kapun et al, 2018;Kapopoulou et al, 2018;Knibb, 1982).…”
Section: Inversion Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is likely that by exploring more natural populations we could identify additional adaptive insertions. We are also missing TEs that could be playing a role in seasonal and altitudinal adaptation, as both dimensions have been shown to be relevant for D. melanogaster [74-76]. Finally, our study is also limited to those insertions present in the reference genome.…”
Section: Discussionmentioning
confidence: 99%
“…As insects are easily manipulated and maintained in the lab, model insect species are widely used for studies of the genetics, molecular biology, environmental physiology, behaviour, and evolution of thermal performance traits [3][4][5][6][7]. Laboratory studies of Drosophila thermal tolerance, for example, have recently allowed for investigation of the molecular or physiological processes that limit their biogeography, and how limits to thermal performance may evolve following changes in abiotic conditions [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%